Optimasi Penjadwalan Ujian Akhir Semester Menggunakan Algoritme Genetika (Studi Kasus: SMAN 5 Malang) - Ni'mah Firsta Cahya Susilo; Budi Darma Setiawan; Agus Wahyu Widodo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Scheduling is an activity with detailed division of time for various purposes in various fields. Scheduling of the semester final exam at SMAN 5 Malang in practice there are still some obstacles such as limited examination supervisors and the distribution of the subjects tested is less suitable. SMAN 5 Malang has applied the exam schedule by dividing subjects based on national examination subjects and other subjects. This study aims to determine the effect of parameter changes on genetic algorithms and find a scheduling solution for the semester final exam at SMAN 5 Malang with a genetic algorithm. Scheduling the final semester exam in this study is divided into subject scheduling and scheduling of exam supervisors. The testing of individual subjects and supervisors is carried out 5 times with population size of 100, number of generations 500 and combination of crossover rate 0.5 and mutation rate 0.5. Testing results in an optimal population for 180 subjects while for supervisors a total of 150. In testing the combination of Cr and Mr values ​​found a combination of optimal values ​​for individual subjects is Cr = 0.7 and Mr = 0.3 and a combination of Cr = 0.6 and Mr = 0.4 for individual supervisors with an optimal number of generations in individual subjects is 200 generations while in individual supervisors is 400 generations.